Pyroelectric influence on lithium niobate during the thermal transition for cryogenic integrated photonics - Thiele, Frederik; Hummel, Thomas; Lange, Nina Amelie; Dreher, Felix; Protte, Maximilian; Bruch, Felix vom; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Materials for Quantum Technology)
Abstract Lithium niobate has emerged as a promising platform for integrated quantum optics, enabling efficient generation, manipulation, and detection of quantum states of light. However, integrating single-photon detectors requires cryogenic operating temperatures, since the best performing detectors are based on narrow superconducting wires. While previous studies have demonstrated the operation of quantum light sources and electro-optic modulators in LiNbO 3 at cryogenic temperatures, the thermal transition between room temperature and cryogenic conditions introduces additional effects that can significantly influence device performance. In this paper, we investigate the generation of pyroelectric charges and their impact on the optical properties of lithium niobate waveguides when changing from room temperature to 25 K, and vice versa. We measure the generated pyroelectric charge flow and correlate this with fast changes in the birefringence acquired through the Sénarmont-method. Both electrical and optical influence of the pyroelectric effect occur predominantly at temperatures above 100 K.
Keywords: General Earth and Planetary Sciences; General Environmental Science

A multi-step framework for the design of a flexible power-to-methane process - Bruns, Bastian; Gross, Michel; Grünewald, Marcus; Bertsch, Valentin; Riese, Julia (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

The Demand for Voluntary Carbon Dioxide Removal – Experimental Evidence from an Afforestation Project in Germany - Bartels, Lara; Kesternich, Martin; Löschel, Andreas (Land Economics)
Keywords: General Earth and Planetary Sciences; General Environmental Science

A Validation Study of the German Versions of the Feeling Scale and the Felt Arousal Scale for a Passive Relaxation Technique (Autogenic Training) - Thorenz, Kristin; Berwinkel, Andre; Weigelt, Matthias (Psychology)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Housing Situations and Local COVID-19 Infection Dynamics – A Case Study With Small-Area Data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik
Keywords: General Earth and Planetary Sciences; General Environmental Science

ElectricGrid.jl - A Julia-based modeling and simulationtool for power electronics-driven electric energy grids - Wallscheid, Oliver; Peitz, Sebastian; Stenner, Jan; Weber, Daniel; Boshoff, Septimus; Meyer, Marvin; Chidananda, Vikas; Schweins, Oliver (Journal of Open Source Software)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Kompetenzentwicklung in der Lehrkräftebildung: der Mehrwert einer digitalen Simulation - Grotegut, Lea; Klingsieck, Katrin B. (ZeHf – Zeitschrift für empirische Hochschulforschung)
Die Förderung diagnostischer Kompetenz in der Lehrer*innenbildung birgt zwei Herausforderungen: Erstens bleibt in großen Lehrveranstaltungen wenig Raum für die notwendige Anwendung theoretischen Wissens, zweitens können Fehlentscheidungen in realen diagnostischen Situationen gravierende negative Folgen für Schüler*innen haben. Eine digitale Simulation kann beiden Herausforderungen begegnen. In diesem Beitrag wurde eine digitale, problemorientierte Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden evaluiert und mit einer textbasierten, problemorientierten und einer lehrendenzentrierten Kontrollgruppe verglichen. Die Ergebnisse zeigen positive Effekte für die digitale Simulation hinsichtlich der selbstbestimmten Motivation, aber einen geringeren Wissenszuwachs im Vergleich zum lehrendenzentrierten Setting. Die Selbstwirksamkeit nahm in allen drei Gruppen zu. Eine digitale Simulation bietet in der untersuchten Form somit einen, wenn auch geringen, Mehrwert für die Lehrkräftebildung im Bereich der Kompetenzentwicklung.
Keywords: General Earth and Planetary Sciences; General Engineering; General Environmental Science

Nonfinancial Reporting and Real Sustainable Change: Relationship Status—It’s Complicated - Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Organization & Environment)
The relationship between nonfinancial reporting and real sustainable change within and beyond organizations is fraught with complication. Furthermore, all facets of the relationship have not been examined equally. The contributions of this special issue made substantive progress in this regard and draw our focus to several remaining complications—in particular, the societal impacts of nonfinancial reporting. With this introduction, we seek to move the conversation forward by proposing a framework that disentangles the linkages between nonfinancial reporting and real sustainable change at multiple levels of analysis. We highlight the distinction between sustainability-related outputs and outcomes that typically materialize at the firm level, and eventually lead to sustainable impact at the societal level. Future research should advance this distinction and scrutinize the impact of real sustainable change beyond firm-level outputs, study the organizational change processes from antecedents to impacts, and examine the interrelationships between different instruments to foster real sustainable change.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

Implications of Algorithmic Wage Setting on Online Labor Platforms: a Simulation-Based Analysis∗ - Dawid, Herbert; Harting, Philipp; Neugart, Michael (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Recalibration of limits to growth: An update of the World3 model - Nebel, Arjuna; Kling, Alexander; Willamowski, Ruben; Schell, Tim (Journal of Industrial Ecology)
Abstract After 50 years, there is still an ongoing debate about the Limits to Growth (LtG) study. This paper recalibrates the 2005 World3‐03 model. The input parameters are changed to better match empirical data on world development. An iterative method is used to compute and optimize different parameter sets. This improved parameter set results in a World3 simulation that shows the same overshoot and collapse mode in the coming decade as the original business as usual scenario of the LtG standard run. The main effect of the recalibration update is to raise the peaks of most variables and move them a few years into the future. The parameters with the largest relative changes are those related to industrial capital lifetime, pollution transmission delay, and urban‐industrial land development time.
Keywords: General Social Sciences; General Environmental Science

Virtual learning environment for teaching the handling of collaborative robots - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel; Unverzagt, Marc; Pottebaum, Jens (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Ammonium enables reversible aqueous Zn battery chemistries by tailoring the interphase - Ma, Lin; Pollard, Travis P.; Zhang, Yong; Schroeder, Marshall A.; Ren, Xiaoming; Han, Kee Sung; Ding, Michael S.; Cresce, Arthur V.; Atwater, Terrill B.; Mars, Julian; Cao, Longsheng; Steinrück, Hans-Georg; et al. (One Earth)
Keywords: Earth and Planetary Sciences (miscellaneous); General Environmental Science

A review of 100% renewable energy scenarios on islands - Meschede, Henning; Bertheau, Paul; Khalili, Siavash; Breyer, Christian (WIREs Energy and Environment)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Enhanced corrosion resistance of epoxy-films on ultra-thin SiOx PECVD film coated laser surface melted Al-alloys - Varghese, J.; Vieth, P.; Xie, X.; Grundmeier, Guido (SN Applied Sciences)
Abstract The influence of ultra-thin SiO x plasma deposited films on the corrosion resistance of adhesive films on a laser surface melted 7075 aluminium alloy was investigated by means of complementary techniques in comparison to the just laser surface melted state. Laser surface melting (LSM) was performed using a continuous wave mode at a wavelength of 1064 nm. Ultra-thin plasma polymer films were deposited from a mixture of hexamethyldisilane (HMDSO), oxygen, and argon by means of an audio-frequency glow discharge. The surface morphology and surface chemistry compositions were investigated by employing field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy (EDX), diffuse reflection infrared Fourier transform spectroscopy, and X-ray photoelectron spectroscopy. The corrosion resistance of plasma polymer coated LSM Al-7075 alloy was studied using linear sweep voltammetry and electrochemical impedance spectroscopy in a chloride-containing electrolyte. The electrochemical studies showed an improved corrosion resistance for plasma film-coated alloys compared to the just laser surface melted state. To study the corresponding surface adhesive properties, the samples were coated with an epoxy amine adhesive. 90°-peel test under humid conditions confirmed the improvement of interfacial wet-adhesion corrosion tests showed a strong improvement of the delamination resistance of adhesives caused by the ultra-thin interfacial SiO x -films.
Keywords: General Earth and Planetary Sciences; General Physics and Astronomy; General Engineering; General Environmental Science; General Materials Science; General Chemical Engineering

Who has the future in mind? Gender, time perspectives, and pro-environmental behaviour - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (Environmental Research Letters)
Abstract An individual’s relation to time may be an important driver of pro-environmental behaviour. We studied whether young individual’s gender and time-orientation are associated with pro-environmental behaviour. In a controlled laboratory environment with students in Germany, participants earned money by performing a real-effort task and were then offered the opportunity to invest their money into an environmental project that supports climate protection. Afterwards, we controlled for their time-orientation. In this consequential behavioural setting, we find that males who scored higher on future-negative orientation showed significantly more pro-environmental behaviour compared to females who scored higher on future-negative orientation and males who scored lower on future-negative orientation. Interestingly, our results are completely reversed when it comes to past-positive orientation. These findings have practical implications regarding the most appropriate way to address individuals in order to achieve more pro-environmental behaviour.
Keywords: Public Health; Environmental and Occupational Health; General Environmental Science; Renewable Energy; Sustainability and the Environment

Overcoming Electron Transfer Efficiency Bottlenecks for Hydrogen Production in Highly Crystalline Carbon Nitride‐Based Materials - Teixeira, Ivo F.; Tarakina, Nadezda V.; Silva, Ingrid F.; Lopez Salas, Nieves; Savateev, Aleksandr; Antonietti, Markus (Advanced Sustainable Systems)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Effects on Process Forces of Individual Milling Tool Edges Depending on the Cutting Angle and Cutting Speed When Milling Cfrp - Clemens, Robin; Barth, Enrico; Uhlmann, Eckart; Zhan, Yingjie; Caylak, Ismail; Mahnken, Rolf (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Orientation-Dependent Indentation Behaviour of Additively Manufactured FeCo Sample: A Quasi In-Situ Study - Pramanik, Sudipta; Tasche, Frederik; Hoyer, Kay-Peter; Schaper, Mirko (Magnetism)
The quasi in-situ indentation behaviour of <110>||BD and <111>||BD-oriented grains in a FeCo alloy is studied in this investigation. The effect of build height on melt pool shape and melt pool size is also studied by finite element method simulations. As the building height increases, the aspect ratio of the elliptical melt pool increases. Correspondingly, the effect of the laser scan speed on the melt pool shape and size is studied by the finite element method, because, as the laser scan speed increases, the aspect ratio of the elliptical melt pool increases, too. The microstructural characterisation of the indentation area before and after indentation is performed by electron backscatter diffraction (EBSD). Based on the EBSD data grain reference orientation deviation (GROD), calculations are performed to describe the effect of indentations on the neighbouring grain orientations. High GROD angles are detected in the neighbouring grain region adjoining the indented grain. An in-depth slip trace analysis shows the activation of all three slip systems ({110}<111>, {112}<111> and {123}<111>) which is also confirmed by slip lines on the sample surface that are detected by laser scanning confocal microscopy. A high concentration of geometrically necessary dislocations (GNDs) are observed on the adjoining area to the indentation. Local surface topography measurements by laser scanning confocal microscopy confirmed the formation of pile-ups near the indentation.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Quality or Quantity? How Structural Parameters Affect Catalytic Activity of Iron Oxides for CO Oxidation - Schlicher, Steffen; Prinz, Nils; Bürger, Julius; Omlor, Andreas; Singer, Christian; Zobel, Mirijam; Schoch, Roland; Lindner, Jörg K. N.; Schünemann, Volker; Kureti, Sven; Bauer, Matthias (Catalysts)
<The replacement of noble metal catalysts by abundant iron as an active compound in CO oxidation is of ecologic and economic interest. However, improvement of their catalytic performance to the same level as state-of-the-art noble metal catalysts requires an in depth understanding of their working principle on an atomic level. As a contribution to this aim, a series of iron oxide catalysts with varying Fe loadings from 1 to 20 wt% immobilized on a γ-Al2O3 support is presented here, and a multidimensional structure–activity correlation is established. The CO oxidation activity is correlated to structural details obtained by various spectroscopic, diffraction, and microscopic methods, such as PXRD, PDF analysis, DRUVS, Mössbauer spectroscopy, STEM-EDX, and XAS. Low Fe loadings lead to less agglomerated but high percentual amounts of isolated, tetrahedrally coordinated iron oxide species, while the absolute amount of isolated species reaches its maximum at high Fe loadings. Consequently, the highest CO oxidation activity in terms of turnover frequencies can be correlated to small, finely dispersed iron oxide species with a large amount of tetrahedrally oxygen coordinated iron sites, while the overall amount of isolated iron oxide species correlates with a lower light-off temperature.
Keywords: Physical and Theoretical Chemistry; Catalysis; General Environmental Science; Key

Motivate the Crowd or Crowd-Them Out? The Impact of Local Government Spending on the Voluntary Provision of a Green Public Good - Bartels, Lara; Kesternich, Martin
Keywords: General Earth and Planetary Sciences; General Environmental Science

More Money or Better Procedures? Evidence From an Energy Efficiency Assistance Program - Chlond, Bettina; Goeschl, Timo; Kesternich, Martin
Keywords: General Earth and Planetary Sciences; General Environmental Science

The Intention-Behavior Gap in Climate Change Adaptation - Kesternich, Martin; Osberghaus, Daniel; Botzen, Willem Jan Wouter
Keywords: General Earth and Planetary Sciences; General Environmental Science

Zusatzkosten der Besteuerung – Eine Analyse des steuerlichen Verwaltungsaufwands und der subjektiv wahrgenommenen Steuerbelastung (An Empirical Analysis of Firms’ Hidden Cost of Taxation) - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren
Keywords: General Earth and Planetary Sciences; General Environmental Science

A comprehensive framework for sustainable closed-loop supply chain network design - Tavana, Madjid; Kian, Hadi; Nasr, Arash Khalili; Govindan, Kannan; Mina, Hassan (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

A multi-distance interval-valued neutrosophic approach for social failure detection in sustainable municipal waste management - Ebadi Torkayesh, Ali; Tavana, Madjid; Santos-Arteaga, Francisco J. (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Effective Attentional Focus Strategies after Anterior Cruciate Ligament Reconstruction: A Commentary - Singh, Harjiv; Gokeler, Alli; Benjaminse, Anne (International Journal of Sports Physical Therapy)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Ausgestaltungs- und Anwendungspotenziale von Virtual und Augmented Reality Technologien im Kontext von Coworking Spaces - Mirbabaie, Milad; Hofeditz, Lennart; Schmid, Leon (HMD Praxis der Wirtschaftsinformatik)
Zusammenfassung Coworking Spaces (CSPs) sind geteilte Arbeitsplätze für Selbstständige, Freelancer*innen, Mikrounternehmen und Startups, die Isolation entgegenwirken und zum interdisziplinären Wissensaustausch anregen können. Jedoch existieren auch Barrieren, die Nutzer*innen davon abhalten, zu anderen Coworker*innen Kontakt aufzunehmen, da oft unklar ist, wann und ob jemand zum kreativen Austausch oder zum Anbieten von Hilfe bereit ist. Durch die Covid-19 Pandemie wurde die Unsicherheit bei der gegenseitigen Kontaktaufnahme noch weiter erschwert und viele CSPs mussten zeitweise schließen. Um Barrieren bei der Kontaktaufnahme zu reduzieren und die interdisziplinäre Zusammenarbeit zu fördern, können Informations- und Kommunikationstechnologien eingesetzt werden. Virtual Reality (VR) und Augmented Reality (AR) sind Technologien, die sich durch einen besonders hohen Grad an Immersion und sozialer Präsenz auszeichnen. Deshalb zeigen wir in diesem Beitrag, wie VR- und AR-Technologien gezielt eingesetzt werden können, um den interdisziplinären Wissensaustausch und Zusammenarbeit sowohl in CSPs als auch ortsunabhängig zu fördern. Dazu präsentieren wir positive Effekte, die durch den Einsatz einer der beiden Technologien im Zusammenhang mit CSPs erzielt werden können und leiten konkrete Gestaltungsempfehlungen für Anwendungsentwickler*innen, Unternehmen sowie Betreiber*innen von CSPs ab. Diese Gestaltungsempfehlungen basieren sowohl auf den neuesten Erkenntnissen aus der Fachliteratur als auch auf Interviews mit Expert*innen aus Forschung und Praxis mit Erfahrung im Bereich CSPs, VR und AR. Unsere Anwendungsszenarien können Entwickler*innen, Unternehmen und Betreiber*innen von CSPs als Grundlage dienen, vom Einsatz beider Technologien zu profitieren.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Affordance-Experimentation: Eine Fallstudie zur Entwicklung von Virtual-Reality-Anwendungsfällen im Unternehmenskontext - Fromm, Jennifer; Slawinski, Elena; Mirbabaie, Milad (HMD Praxis der Wirtschaftsinformatik)
Zusammenfassung Durch technologische Fortschritte in den letzten Jahren ist Virtual Reality erschwinglicher und benutzerfreundlicher geworden, sodass Unternehmen die Einführung der Technologie verstärkt in Betracht ziehen. Ihren Aufschwung erlebte die Technologie jedoch durch die Unterhaltungs- und Spieleindustrie, weshalb sich für Unternehmen die Frage nach sinnvollen Anwendungsfällen stellt. Nach der Affordance-Experimentation-Actualization-Theorie ist insbesondere bei neu aufkommenden Technologien eine Experimentierphase notwendig, um Handlungsmöglichkeiten aufzudecken und daraus Anwendungsfälle zu generieren. Dieser Artikel präsentiert die Ergebnisse einer Fallstudie in einem Unternehmen, das sich während der Studie in der Experimentierphase befand. Durch Interviews mit acht Beschäftigten und einem Vertriebspartner konnten drei Handlungsmöglichkeiten für Virtual Reality im Unternehmenskontext und eine zuvor nicht bekannte Aktivität der Experimentierphase identifiziert werden. Damit erweitert die Studie bisherige Forschung zur Experimentierphase und zeigt Unterschiede im Vergleich zu anderen innovativen Technologien auf, die in vorherigen Studien untersucht wurden. Für Unternehmen bietet die Studie wertvolle Einblicke in die erfolgreiche Gestaltung der Experimentierphase als Vorbereitung auf die Implementierung.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Sustainable oxidation catalysis supported by light: Fe-poly (heptazine imide) as a heterogeneous single-atom photocatalyst - da Silva, Marcos A.R.; Silva, Ingrid F.; Xue, Qi; Lo, Benedict T.W.; Tarakina, Nadezda V.; Nunes, Barbara N.; Adler, Peter; Sahoo, Sudhir K.; Bahnemann, Detlef W.; López-Salas, Nieves; Savateev, Aleksandr; Ribeiro, Caue; et al. (Applied Catalysis B: Environmental)
Keywords: Process Chemistry and Technology; General Environmental Science; Catalysis

Kompetenzorientiertes E-Assessment für die grafische, konzeptuelle Modellierung - Striewe, Michael; Forell, Martin; Houy, Constantin; Pfeiffer, Peter; Schiefer, Gunther; Schüler, Selina; Soyka, Chantal; Stottrop, Tobias; Ullrich, Meike; Fettke, Peter; Loos, Peter; Oberweis, Andreas; et al. (HMD Praxis der Wirtschaftsinformatik)
Zusammenfassung In vielen Bereichen der Wirtschaftsinformatik spielt die Erstellung konzeptueller Modelle unter Verwendung grafischer Modellierungssprachen eine wichtige Rolle. Entsprechend wichtig ist eine fundierte Grundausbildung, die sich an den benötigten Modellierungskompetenzen orientiert und daher neben theoretischen auch praktische Aspekte der konzeptuellen Modellierung in den Blick nimmt. Der vorliegende Beitrag stellt erste Ergebnisse aus dem KEA-Mod-Projekt vor, das sich mit der Erstellung eines „digitalen Fachkonzepts“ im Bereich der grafischen, konzeptuellen Modellierung befasst. Kernstück dieses Fachkonzepts ist die Unterstützung der Grundausbildung in der grafischen, konzeptuellen Modellierung durch eine kompetenzorientierte E‑Assessment-Plattform mit automatisierten und individuellen Bewertungs- und Feedbackmöglichkeiten.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Sustainable oxidation catalysis supported by light: Fe-poly (heptazine imide) as a heterogeneous single-atom photocatalyst - da Silva, Marcos A.R.; Silva, Ingrid F.; Xue, Qi; Lo, Benedict T.W.; Tarakina, Nadezda V.; Nunes, Barbara N.; Adler, Peter; Sahoo, Sudhir K.; Bahnemann, Detlef W.; Lopez Salas, Nieves; Savateev, Aleksandr; Ribeiro, Caue; et al. (Applied Catalysis B: Environmental)
Keywords: Process Chemistry and Technology; General Environmental Science; Catalysis

In Krisen erzählen – von Krisen erzählen. Sprachliche, literarische und mediale Dimensionen.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Mehrdeutigkeiten
Keywords: General Earth and Planetary Sciences; General Environmental Science

Thermodynamic Analysis of the Self‐Assembly of Pseudo Isocyanine Chloride in the Presence of Crowding Agents - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (ChemSystemsChem)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Electric and conventional vehicle usage in private and car sharing fleets in Germany - Habla, Wolfgang; Huwe, Vera; Kesternich, Martin (Transportation Research Part D: Transport and Environment)
Keywords: General Environmental Science; Transportation; Civil and Structural Engineering

The Head-Fake Effect in Basketball Is Based on the Processing of Head Orientation, but Not on Gaze Direction - Weigelt, Matthias; Güldenpenning, Iris; Steggemann-Weinrich, Yvonne (Psychology)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Intergenerationelle Beziehungen in der Familie - Buhl, Heike M.; Sommer, Sabrina (Psychotherapie im Alter)
Beziehungen zwischen Erwachsenen und ihren Eltern sind durch Interdependenzen und Dependenzen gekennzeichnet. Während das Zusammenleben von Familien mit Kindern im mittleren Erwachsenenalter dabei ganz überwiegend durch Interdependenz geprägt ist, nehmen im Alter Dependenzen durch gesundheitliche Beeinträchtigungen der Eltern zu. Mit Blick darauf werden im Artikel behaviorale, kognitive und emotionale Merkmale von Eltern-Kind-Beziehungen erläutert und theoretisch in zentrale Konzepte eingebettet. Das Verhalten ist durch Solidarität zwischen den Generationen, aber auch durch Aspekte des Einflusses innerhalb der Beziehung und aufeinander, gekennzeichnet. Um Familienkognitionen zu beschreiben, werden die verwandten Konzepte der Individuation und der filialen Reife herangezogen. Verhalten, wie auch Kognitionen, sind eng mit dem dritten Beziehungsmerkmal, der Affektivität verknüpft, das neben positiven auch negative Gefühle sowie Ambivalenzen umfasst.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Neither demarcation nor confrontation. Finding a critical position towards right-wing populism - Haker, Christoph; Otterspeer, Lukas (Zeitschrift für Weiterbildungsforschung)
Abstract Right-wing populism has strongly polarizing effects in politics, education and science—a problem which this article aims to adress. Instead of claiming a demarcation between science and education on the one hand and right-wing populist ideology on the other, we initially focus on continuities. At the same time, we are concerned with finding a critical distance towards right-wing populism. Using the theoretical framework of boundary-work we therefore analyse a case of right-wing populist educational and scientific efforts. Boundary-work can occur in an institutional, content-related and epistemic dimension. While we identify strong continuities in the institutional and content-related dimensions, we see the main difference in the epistemic dimension. In conclusion, we use the results of our analysis to develop a critical position as scientists and educationists towards right-wing populism, drawing consequences for the epistemic, content-related and institutional dimensions.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Sprachstrukturelle Modelle. Linguistische, spracherwerbsorientierte und didaktische Zugänge - Tophinke, Doris; Topalovic, Elvira; Rohlfing, Katharina J. (Mitteilungen des Deutschen Germanistenverbandes)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Deutschdidaktik 2000–2018. Debatten – Entwicklungen – Perspektiven
Keywords: General Earth and Planetary Sciences; General Environmental Science

Nähe-Distanz als multimodaler Strukturierungsraum: Empirische Daten zum vorschulischen Schriftspracherwerb - Topalović, Elvira; Drepper, Laura (Mitteilungen des Deutschen Germanistenverbandes)
Keywords: General Earth and Planetary Sciences; General Environmental Science

The value of signals: Do self-declaration and certification generate price premiums for organic and biodynamic wines? - Fanasch, Patrizia; Frick, Bernd (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

Political embeddedness and the diffusion of corporate social responsibility practices in China: A trade-off between financial and CSR performance? - Wang, Zhi; Reimsbach, Daniel; Braam, Geert (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Optimization of the energy supply in the plastics industry to reduce the primary energy demand - Dunkelberg, Heiko; Wagner, Johannes; Hannen, Conrad; Schlüter, Alexander; Phan, Long; Hesselbach, Jens; Lin, Cheng-Xian (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

A holistic approach to energy efficiency assessment in plastic processing - Schlüter, Alexander; Rosano, Michele B. (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

Adaptive Förderung zur Vorbereitung auf den Übergang vom Elementar- in den Primarbereich am Beispiel des Bereichs Mathematik - Bruns, Julia; Eichen, Lars (Frühe Bildung)
Die vorliegende quasi-experimentelle Querschnittsuntersuchung verfolgt das Ziel, adaptive Förderleistungen elementarpädagogischer Fachpersonen zu erfassen und Zusammenhänge mit anderen Komponenten elementarpädagogischer Arbeit aufzudecken. Im Zentrum steht die Frage: Welcher Zusammenhang zeigt sich zwischen der Beobachtungsintensität, den diagnostischen Fähigkeiten und der Qualität der adaptiven Förderpraxis im Elementarbereich? Fokussiert wird die adaptive Förderleistung einer Teilstichprobe mit n = 31 Fachpersonen in Bezug auf die Teilstichprobe von n = 62 Kinder. Dazu werden verschiedene Methoden auf Kinder- und Fachpersonenebene im Sinne eines mixed-methods Designs miteinander verknüpft (Mathematiktest ‚zahlenstark‘, standardisierte Beobachtung, standardisiertes Interview). Die Ergebnisse zeigen, dass keiner Fachperson eine optimale Förderung zweier Kinder gelingt. Im Hinblick auf den Übergang zwischen Elementar- und Primarbereich kann gefolgert werden, dass die Kinder unzureichend in ihren individuellen Bildungsprozessen begleitet werden.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Extreme weather experiences and climate change beliefs in China: An econometric analysis - Dai, Jing; Kesternich, Martin; Löschel, Andreas; Ziegler, Andreas (Ecological Economics)
Keywords: Economics and Econometrics; General Environmental Science

Organizations, Climate Change, and Transparency - Hahn, Rüdiger; Reimsbach, Daniel; Schiemann, Frank (Organization & Environment)
The debate surrounding climate change often centers on companies’ contributions to global warming, which has led to an increase in the importance of carbon disclosure. We evaluate the current state of related research and identify its trends, coherences, and caveats via a systematic literature review. Sociopolitical theories of disclosure, economic theories of disclosure, and institutional theory serve as the main theoretical anchors for our exploration. The existing research emphasizes the determinants and, to a lesser extent, effects of carbon disclosure, as well as the associated regulatory issues such as voluntary versus mandatory disclosure. Additionally, we discuss related topics, such as assurance and risks. We find that a large portion of scholarly work provides no link to theory, despite the fact that such links can be identified, for example, from the financial disclosure literature. Finally, we report on the established knowledge and examine the need for additional research.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science